Communication as a Moral Calling in the Algorithmic Era: Reactualizing Inter Mirifica in Adolescent Character Education - Losianus Harjon (Communigate, 2025)
Digital communication ideally constitutes a formative arena that cultivates the moral and intellectual maturation of adolescents as active constituents of the digital generation. Yet prevailing social media practices are frequently characterised by the proliferation of misinformation, cyberbullying, unrestrained self-disclosure, and compulsive validation-seeking, tendencies that progressively erode moral accountability and compromise the coherent development of personal identity. This study interrogates the principle of responsibility in digital communication as a normative substrate for adolescent character formation, and proposes a conceptual framework for embedding both personal and collective accountability into the fabric of everyday social media engagement. Employing a qualitative descriptive-analytical methodology grounded in systematic literature review, conceptual excavation, and critical reflection on the prevailing dynamics of digital communication, the study delineates three cardinal dimensions of responsibility: personal responsibility, encompassing self-regulation and the rigorous verification of information; social responsibility, entailing a heightened awareness of public ramifications and an unwavering commitment to the inviolability of human dignity; and structural responsibility, pertaining to the constitutive roles of the family, educational institutions, government, the Church, and civil society in furnishing ethical guidance and regulatory oversight. Collectively, these findings substantiate the claim that responsibility-centred character education is both contextually urgent and normatively indispensable for adolescents navigating the complexities of the digital milieu. Responsible digital communication thus emerges as a strategic trajectory for cultivating a generation of reflective, autonomous, and integrity-driven youth capable of engaging thoughtfully and ethically with the profound challenges posed by contemporary digital technology.